Corni Fructus Alleviates UUO-Induced Renal Fibrosis via TGF-β/Smad Signaling. (6th May 2022) - Lee, Jin A.; Shin, Mi-Rae; Roh, Seong-Soo
Abstract : Renal fibrosis is a type of chronic kidney disease (CKD) induced by infiltration of inflammatory cells, myofibroblast accumulation, and ECM production in the kidney. From a long time ago, Corni Fructus (CF) is known to supplement the liver and kidney with its tepid properties. In this study, we investigated the renal protective mechanism of CF, which is known to supplement the kidney, in rat model of unilateral ureteral obstruction (UUO). After inducing UUO through surgery, the group was separated (n = 8 ) and the drug was administered for 2 weeks; normal rats (normal), water-treated UUO rats (control), CF 100 mg/kg-treated UUO rats (CF100), and CF 200 mg/kg-treated UUO rats (CF200). As a result of histopathological examination of kidney tissue with H&E, MT, and PAS staining, it was confirmed that the infiltration of inflammatory cells and the erosion of collagen were relatively decreased in the kidneys treated with CF. Also, CF significantly reduced the levels of MDA and BUN in serum. As a result of confirming the expression of the factors through western blotting, CF treatment significantly reduced the expression of NADPH oxidase and significantly regulated the AMPK/LKB1/NF- κ B pathway associated with inflammation. In addition, it downregulated the expression of major fibrotic signaling factors, such as α -SMA, collagen I, MMP-2, and TIMP-1, and significantly regulated the TGF- β 1/Smad pathway, which is known as a major regulator of renal fibrosis. Taken together, these findings indicate that CF can alleviate renal fibrosis by regulating the TGF- β 1/Smad pathway through inhibition of oxidative stress in UUO.